Clinical characteristics and outcomes of PTLD after kidney transplant: a single center experience - Afonso, Rita (2024)
Post-Transplant Lymphoproliferative Disorder (PTLD) is a serious and potentially fatal complication of immunosuppression in kidney transplantation. Given the rarity of this entity, a high index of suspicion is necessary. We aimed to review the incidence, clinical presentation, histological subtypes, treatment, patient and graft survival of PTLD in kidney transplant patients in our unit.